Pengaruh Penggunaan Awetan Basah Filum Moluska dan Echinodermata dengan Inquiry Learning terhadap Hasil Belajar Siswa - Siburian, Isyulianto Andika Tua; Sikumbang, Darlen; Yolida, Berti (Assimilation: Indonesian Journal of Biology Education, 2019)
This study aims to determine the effect of use of wet preservation Phylum of Molluscs and Echinoderms with Inquiry Learning on student learning outcomes. The method of this study was quasi-experimental with nonequivalent pretest-posttest control group design. The research samples were students of class X MIPA 1 and X MIPA 2 which were to 56 students that were selected by the Total Sampling technique. The type of data used were quantitative data and qualitative data. The instrument used in this study was in the form of multiple-choice questions, with the independent sample t-test SPSS 17.0 data processing technique. The results showed that the use of wet preservation Phylum of Molluscs and Echinoderms differed significantly on student learning outcomes in the experimental class with the control class. The average N-gain in the experimental class was 0.58, while the control class was 0.39, while the results of student responses to wet preservation Phylum of Molluscs and Echinoderms with Inquiry Learning have a good (78,57%) and very good (84,78%).